2016
DOI: 10.1038/cdd.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

NRAGE is involved in homologous recombination repair to resist the DNA-damaging chemotherapy and composes a ternary complex with RNF8–BARD1 to promote cell survival in squamous esophageal tumorigenesis

Abstract: NRAGE, a neurotrophin receptor-interacting melanoma antigen-encoding gene homolog, is significantly increased in the nucleus of radioresistant esophageal tumor cell lines and is highly upregulated to promote cell proliferation in esophageal carcinomas (ECs). However, whether the overexpressed NRAGE promotes cell growth by participating in DNA-damage response (DDR) is still unclear. Here we show that NRAGE is required for efficient double-strand breaks (DSBs) repair via homologous recombination repair (HRR) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…H2A.X phosphorylation is the result of DNA damage [32,33], and thus, we speculated that increased DOX-induced H2A.X phosphorylation by ATG reflects an increase in DNA, and that this enhanced MDA-MB-231 cell death ( Figure 1C). Cell death by DNA damage is primarily caused by a failure to repair DNA [34,35], and survivin and RAD51 play important roles in DNA repair [36,37]. Hence, the ATG/DOX-induced suppressions of survivin and RAD51 protein levels suggests increased cell death was due to an inability to repair DNA.…”
Section: Discussionmentioning
confidence: 99%
“…H2A.X phosphorylation is the result of DNA damage [32,33], and thus, we speculated that increased DOX-induced H2A.X phosphorylation by ATG reflects an increase in DNA, and that this enhanced MDA-MB-231 cell death ( Figure 1C). Cell death by DNA damage is primarily caused by a failure to repair DNA [34,35], and survivin and RAD51 play important roles in DNA repair [36,37]. Hence, the ATG/DOX-induced suppressions of survivin and RAD51 protein levels suggests increased cell death was due to an inability to repair DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection of siRNAs and establishment of stable cell lines were all performed according to our previous experimental procedures. 5,11 Cell Counting Kit-8 assay…”
Section: Small-interfering Rna and Cell Transfectionmentioning
confidence: 99%
“…The survival of DNA-damaged cancer cells is determined by whether cancer cells can repair damage to DNA (44,45). The current study revealed that the viability of Capan-1 cells was decreased and not in Panc-1 cells, and the difference was associated with a decrease of RAD51 expression.…”
Section: Discussionmentioning
confidence: 52%
“…The fate of DNA-damaged cancer cells by chemotherapy and radiotherapy is determined by whether DNA damage is repaired (44,45). Therefore, the activities of DNA repair enzymes have been demonstrated to be closely associated with cell death and cell cycle arrest (45).…”
Section: Pb Irradiation Decreases Rad51 Expression In Capan-1 Cellsmentioning
confidence: 99%